2012
DOI: 10.1210/en.2012-1019
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Significant Metabolic Abnormalities in Mice with Liver-Specific Disruption of 11β-Hydroxysteroid Dehydrogenase Type 1

Abstract: Glucocorticoids (GC) are implicated in the development of metabolic syndrome, and patients with GC excess share many clinical features, such as central obesity and glucose intolerance. In patients with obesity or type 2 diabetes, systemic GC concentrations seem to be invariably normal. Tissue GC concentrations determined by the hypothalamic-pituitary-adrenal (HPA) axis and local cortisol (corticosterone in mice) regeneration from cortisone (11-dehydrocorticosterone in mice) by the 11β-hydroxysteroid dehydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 56 publications
6
68
0
2
Order By: Relevance
“…However, this discrepancy might be attributable to a compensatory production of corticosterone by other tissues and a downregulation of 11b- HSD2 by the liver. In fact, the authors detected around 40% cortisol levels in knockout mice relative to control mice after cortisone challenge 40 . In addition, Dex has been reported to render non-haematological cancer cells more resistant to antitumour drugs [41][42][43][44] .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, this discrepancy might be attributable to a compensatory production of corticosterone by other tissues and a downregulation of 11b- HSD2 by the liver. In fact, the authors detected around 40% cortisol levels in knockout mice relative to control mice after cortisone challenge 40 . In addition, Dex has been reported to render non-haematological cancer cells more resistant to antitumour drugs [41][42][43][44] .…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, our findings suggest that the downregulation of 11b-HSD1 and upregulation of 11b-HSD2 might generate a profound effect on gluconeogenesis in malignant hepatocytes via regulating GC activities. Recently, Lavery et al 40 found that hepatic PEPCK and G6Pase were expressed in the liver-specific 11b-HSD1 knockout mice, implicating that the loss of 11b-HSD1 does not have a profound effect on gluconeogenesis. However, this discrepancy might be attributable to a compensatory production of corticosterone by other tissues and a downregulation of 11b- HSD2 by the liver.…”
Section: Discussionmentioning
confidence: 99%
“…All procedures were carried out in accordance with the UK Animals (Scientific Procedures) Act 1986. Six-week-old male global (GKO) (C57BL/6) (31), liver-specific (LKO) (C57BL/6J/129SvJ) (19), and adipose-specific (FKO) C57BL/6J (SI Text) 11β-HSD1 KO mice, with WT controls, had ad libitum access to standard chow and drinking water supplemented with either CORT (100 μg/mL, 0.66% ethanol), 11DHC (100 μg/mL, 0.66% ethanol), or vehicle (0.66% ethanol) for 5 wk. Treatments were replaced twice weekly.…”
Section: Methodsmentioning
confidence: 99%
“…Details with respect to the generation of these transgenic lines are presented in ref. 19, SI Text, and Fig. S6 A-E.…”
mentioning
confidence: 99%
“…Genetic knockdown of 11b-HSD1 (69) as well as pharmacological inhibition (70) decreases hepatic steatosis. Interestingly, this may not reflect changes in hepatic GC availability as liver-specific 11b-HSD1 deletion does not impact significantly on metabolic phenotype and this may point to a more crucial role of GC metabolism within adipose tissue (71). The role of the A-ring reductases has been less well explored, although there is some evidence to suggest that deletion of 5aR type 1 increases the risk of development of hepatic steatosis (72).…”
Section: Glucocorticoidsmentioning
confidence: 99%